FAKTOR-FAKTOR YANG MEMPENGARUHI LOYALITAS KONSUMEN MELALUI KEPUASAN KONSUMEN: ANALISIS KUALITAS LAYANAN, KEPERCAYAAN MEREK, DAN PENGALAMAN KONSUMEN - Ni Ketut Karwini; Ni Wayan Ana Rahita Handayani; Tettie Setiyarti; Ni Ketut Laswitarni; Ida Ayu Trisna Wijayanthi (Majalah Ilmiah DIAN ILMU, 2025)
This study aims to develop a hypothesis regarding the factors that affect consumer loyalty with the intervening role of consumer satisfaction, especially in the hospitality sector. The novelty of this study lies in the integration of three main variables, namely service quality, brand trust, and consumer experience, which are analyzed simultaneously in influencing consumer loyalty through consumer satisfaction in the hospitality sector in Indonesia. The method used is qualitative with a qualitative descriptive literature review approach. Data was collected through the review of various relevant academic articles and books, sourced from reputable databases such as Thomson Reuters, Springer, Taylor & Francis, Scopus Q2–Q4, Emerald, Elsevier, Sage, Web of Science, Sinta 2–5 Journal, DOAJ, EBSCO, Google Scholar, Copernicus, and other digital references. The analysis technique used is a comparative analysis of the results of previous research to identify similarities and differences in findings. The results of this study are that the variables of service quality, brand trust and consumer experience affect consumer loyalty, either directly or indirectly through consumer satisfaction. The limitations of this study are limited because they only use a descriptive qualitative approach based on literature review, so they do not involve empirical data directly from hospitality consumers. The findings of this study have important implications for hotel management. First, improving the quality of consistent, responsive, and empathetic service must be a priority because it has been proven to increase consumer satisfaction and loyalty.